Development and validation of the nutrition literacy scale for Chinese gout patients - Wenjuan Zhang; Jiaqi Wang; Yan Wu; Yinglan Xia; Ziyu Sun; Yuhong Wu (PLoS ONE, 2025)
Background Nutrition literacy is essential for the self-management and treatment of gout patients. However, to date, there is no appropriate scale to measure the level of nutrition literacy gout patients in China. Objective This study objective to develop and psychometric nutrition literacy scale for patients with gout. Methods Using item development and psychological assessment. First, literature review, brainstorming, delphi study, and pr-survey were used to construct draft of the nutrition literacy scale for patients with gout. Second, 526 patients with gout underwent scale-based surveys. Item analysis and exploratory factors were used to optimize the scale. Confirmatory factor analysis was used to verify the structure of the scale, including the goodness of fit of the model, convergent validity, and discriminant validity. Subsequently, the reliability of the scale was tested using cronbach’s α coefficient and test-retest reliability. Results The formal scale contains 5 dimensions: nutrition belief, nutrition knowledge, nutrition information acquisition ability, nutrition information interaction ability, nutrition information criticism ability, and 26 items. The overall content validity of the scale is 0.933. Exploratory factor analysis extracted 5 factors with a cumulative variance contribution of 82.18%. Confirmatory factor analysis showed that the scale structure was well fitted, with good convergent and discriminant validity. The overall cronbach’s α coefficient of this scale was 0.873, and the cronbach’s α coefficients of the dimensions were 0.861 ~ 0.980, and the overall re-test reliability was 0.864, and the re-test reliabilities of the dimensions were 0.881 ~ 0.981. Conclusion Nutrition Literacy Scale for Gout Patients has good reliability and validity. It is suitable for the evaluation of nutrition literacy level in relevant population.